Defective sarcomere assembly in smyd1a and smyd1b zebrafish mutants. Issue 5 (28th February 2019) - Cai, Mengxin; Han, Lichen; Liu, Lusha; He, Feng; Chu, Wuying; Zhang, Jianshe; Tian, Zhenjun; Du, Shaojun
ABSTRACT: Two smyd1 paralogues, smyd1a and smyd1b, have been identified in zebrafish. Although Smyd1b function has been reported in fast muscle, its function in slow muscle and the function of Smyd1a, in general, are uncertain. In this study, we generated 2 smyd1a mutant alleles and analyzed the muscle defects in smyd1a and smyd1b single and double mutants in zebrafish. We demonstrated that knockout of smyd1a alone had no visible effect on muscle development and fish survival. This was in contrast to the smyd1b mutant, which exhibited skeletal and cardiac muscle defects, leading to early embryonic lethality. The smyd1a and smyd1b double mutants, however, showed a stronger muscle defect compared with smyd1a or smyd1b mutation alone, namely, the complete disruption of sarcomere organization in slow and fast muscles. Immunostaining revealed that smyd1a; smyd1b double mutations had no effect on myosin gene expression but resulted in a dramatic reduction of myosin protein levels in muscle cells of zebrafish embryos. This was accompanied by the up‐regulation of hsp40 and hsp90‐α1 gene expression. Together, our studies indicate that both Smyd1a and Smyd1b partake in slow and fast muscle development although Smyd1b plays a dominant role compared with Smyd1a.—Cai, M., Han, L., Liu, L., He, F., Chu, W., Zhang, J., Tian, Z., Du, S. Defective sarcomere assembly in smyd1a and smyd1b zebrafish mutants. FASEB J. 33, 6209–6225 (2019). www.fasebj.org